Manganese slag-biochar composite catalyst as well as preparation method and application thereof
Through the combined use of manganese slag, oil tea shell biochar composite catalyst and PMS, the problems of cumbersome preparation, large reagent consumption and recontamination in the existing wastewater treatment methods are solved, and the efficient degradation of organic matter in wastewater and the possibility of large-scale application is achieved.
Patent Information
- Application Number
- CN202411827711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
In the existing wastewater treatment methods, the preparation process of biochar is cumbersome, the reagents are consumed heavily, and it depends on adsorption, which can easily lead to recontamination and make it difficult to achieve large-scale application.
The compound catalyst of manganese slag and oil tea shell biochar is used to degrade organic matter under Fenton-like reaction, especially the degradation effect on ethyl hydroxybenzoate in wastewater, and is used in combination with activated persulfate (PMS) to improve the degradation efficiency.
It achieves efficient degradation of organic matter in wastewater, significantly improves the degradation rate, avoids re-contamination, and is simple in process and low in cost, making it suitable for large-scale applications.
Smart Images

Figure CN119657118A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of wastewater treatment, and in particular to a manganese slag-biochar composite catalyst and a preparation method and application thereof. Background Art
[0002] Advanced oxidation processes (AOPs) can generate highly reactive oxygen species (ROS), which can efficiently and quickly remove refractory organic pollutants, and are easy to operate and highly stable. Metal / carbon composites can significantly improve the ability to remove pollutants, such as biochar / nano-alumina composites that can be used to efficiently remove methylene blue from water.
[0003] However, this method, which is obtained by impregnating biochar into a pure chemical solution system, still has problems such as complicated preparation process and high reagent consumption. In the process of removing organic matter, it mainly relies on adsorption. In the environment, it is very easy to desorb and cause re-pollution, making it difficult to achieve large-scale application.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a manganese slag-biochar composite catalyst and a preparation method thereof. The composite catalyst realizes the compounding of manganese slag and tea oil biochar, degrades organic matter under a Fenton-like reaction, and has a particularly good degradation effect on ethyl hydroxybenzoate in wastewater.
[0006] The second purpose of the present invention is to provide an application of the above-mentioned manganese slag-biochar composite catalyst, which is used to activate peroxymonosulfate (PMS) to degrade organic matter in wastewater, and has a good application.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] The present invention provides a method for preparing a manganese slag-biochar composite catalyst, comprising the following steps:
[0009] Add manganese slag and tea oil shell biochar powder to Na2CO3 solution and react for more than 30 minutes, then add HNO3 and continue to react for more than 30 minutes, then dry at 100-130℃ for more than 8 hours, and continue pyrolysis at 450-550℃ for more than 3 hours.
[0010] Preferably, as a further feasible solution, during the pyrolysis process, the temperature is raised to a specified pyrolysis temperature at a rate of 10-12°C / min by passing N2.
[0011] In the scheme of the present invention, two common wastes, camellia shells and electrolytic manganese slag, are used as raw materials, which are low in cost and simple in preparation process, and are conducive to large-scale production. Moreover, the catalyst prepared by using the two can better achieve the degradation of organic matter in wastewater. Since manganese slag contains a large amount of transition metals, such as manganese, iron and other oxides, which are excellent PMS activators, the synergistic effect between these oxides and biochar makes its catalytic performance better than that of single manganese slag and camellia biochar, and can promote the degradation of organic matter in water. Therefore, the synergistic use of the two can better improve the degradation effect of organic matter in wastewater.
[0012] Preferably, as a further feasible solution, the manganese slag is pretreated by soaking it in deionized water for more than 4 hours and drying it at 100-130° C. for more than 12 hours.
[0013] Preferably, as a further feasible solution, before the pretreatment, the manganese slag is pre-treated with a treatment agent for more than 1 hour, and then a curing agent is added to the manganese slag for calcination at 200-300° C. for more than 3 hours.
[0014] Preferably, as a further feasible scheme, the method for preparing the tea oil shell biochar powder comprises: crushing and grinding the tea oil shell, washing it with deionized water for more than three times, drying it, heating it at a rate of 10°C / min under N2 conditions, and continuously pyrolyzing it at 500-600°C for more than 3 hours.
[0015] Preferably, as a further feasible solution, the curing agent is any one or more of quartz and starch.
[0016] Preferably, as a further feasible solution, the treatment agent is any one of sodium carbonate, quicklime, and oxalic acid, or a combination of several of them.
[0017] In order to further improve the treatment effect of the catalyst, it is best to pre-treat the two raw materials first. Specifically, the manganese slag is first treated with a treatment agent and then a curing agent is added and roasted. The significance of doing so is to prevent the ammonia nitrogen in the manganese slag from entering the water and causing secondary pollution. In addition, curing the calcium, sulfur, etc. in the manganese slag is beneficial to improving its catalytic degradation performance of organic matter in water. The pre-treatment of the tea oil shell is to remove the ash inside, which is more conducive to improving the obtained biochar with better adsorption performance. Therefore, it can be seen that after the tea oil shell is crushed and dried, the present invention also performs a pyrolysis treatment on it for more than 3 hours. The reason for this operation is also to improve its adsorption effect.
[0018] The present invention also provides further applications of the manganese slag-biochar composite catalyst prepared by the above preparation method, specifically including:
[0019] The composite catalyst and PMS are added to the wastewater for degradation, the degradation reaction temperature is 20-30° C., and the degradation reaction time is 150-200 minutes.
[0020] Preferably, as a further feasible solution, the composite catalyst is added at a concentration of 2 g / L or more, and the PMS addition amount is 5 mM / L or more. Preferably, the composite catalyst is added at a concentration of 3 g / L, and the PMS addition amount is 10 mM / L.
[0021] In the wastewater treatment application process of the present invention, a manganese slag-tea-oil biochar composite catalyst / PMS heterogeneous Fenton-like system is used to degrade organic wastewater. The composite catalyst has a high catalytic activity for the decomposition of PMS and can promote the efficient oxidation degradation of organic pollutants by PMS.
[0022] The above application uses manganese slag-tea-oil biochar composite catalyst / PMS heterogeneous Fenton-like system to degrade organic wastewater, treating waste with waste. It not only has a wide degradation concentration range, strong degradation ability, and mild reaction conditions, but also effectively alleviates the environmental pressure caused by excessive stacking of electrolytic manganese slag. At the same time, the treated slag after large-scale treatment can be further utilized as a resource. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] By reading the detailed description of the preferred embodiment below, various other advantages and benefits will become clear to those of ordinary skill in the art. The accompanying drawings are only used for the purpose of illustrating the preferred embodiment and are not considered to be limitations of the present invention. In addition, the same reference symbols are used to represent the same components throughout the accompanying drawings.
[0024] Figure 1 It is a graph showing the degradation rate of wastewater of various embodiments of the present invention and comparative examples;
[0025] Figure 2 The XRD patterns of Example 1 of the present invention and the original manganese slag are shown in FIG. DETAILED DESCRIPTION
[0026] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] Example 1
[0028] (1) Pretreatment of manganese slag: first add quicklime for 1 hour, then add starch and roast at 200°C for 3 hours, soak in deionized water for 4 hours, and dry at 100°C for 12 hours;
[0029] (2) The tea oil shell was crushed, ground, washed three times with deionized water, dried, loaded into a quartz tube, placed in a high-temperature tube furnace, and heated at a rate of 10 °C / min to 600 °C for 4 h under N2 conditions to obtain raw tea oil shell biochar.
[0030] (3) The manganese slag treated in step (1) and the original tea oil shell biochar obtained in step (2) were used to prepare a composite catalyst: the manganese slag and tea oil shell biochar were combined by a one-pot method and a thermal decomposition process to prepare a manganese slag-tea oil biochar composite catalyst, the same mass of manganese slag and tea oil shell biochar powder were added to 50mL Na2CO3 solution (5g / L) and reacted in an oscillator for 30min, then 1mL HNO3 was added to a beaker, the reaction was continued for 30min, and then dried at 130°C for 9h, and then ground and sieved through a 100-mesh sieve. After grinding, it was loaded into a quartz tube and placed in a high-temperature tube furnace. The temperature was raised at a rate of 12°C / min under the condition of N2 (10mL / min) to 450°C for continuous pyrolysis for 4h to obtain a manganese slag-tea oil biochar composite catalyst. The specific XRD pattern is as follows Figure 2 shown.
[0031] (4) Degradation of organic matter (ethyl p-hydroxybenzoate): The pH value of organic wastewater was 6.89; the concentration of manganese slag-tea oil biochar composite catalyst added to organic wastewater was 2 g / L; the amount of PMS added was 5 mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20 mg / L; during the degradation reaction, the degradation reaction temperature was 25 °C, the degradation reaction time was 180 min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180 min, the degradation rate of ethyl p-hydroxybenzoate was 68% (e.g. Figure 1 shown).
[0032] Example 2
[0033] (1) Pretreatment of manganese slag: first add sodium carbonate for 1 hour, then add quartz and roast at 300°C for 3 hours, soak in deionized water for 5 hours, and dry at 130°C for 14 hours;
[0034] (2) The tea oil shell was crushed, ground, washed three times with deionized water, dried, loaded into a quartz tube, placed in a high-temperature tube furnace, and heated at a rate of 10 °C / min to 500 °C for 3 h under N2 conditions to obtain raw tea oil shell biochar.
[0035] (3) The manganese slag treated in step (1) and the original tea oil shell biochar obtained in step (2) are used to prepare a composite catalyst: the manganese slag and tea oil shell biochar are combined by a one-pot method and a thermal decomposition process to prepare a manganese slag-tea oil biochar composite catalyst, the same mass of manganese slag and tea oil shell biochar powder are added to 50mL Na2CO3 solution (5g / L) and reacted in an oscillator for 30min, then 1mL HNO3 is added to a beaker, the reaction is continued for 30min, and then dried at 110°C for 8h, and then ground and sieved through a 100-mesh sieve. After grinding, it is loaded into a quartz tube and placed in a high-temperature tube furnace. The temperature is increased at a rate of 10°C / min under the condition of N2 (10mL / min) to 500°C for continuous pyrolysis for 3h to obtain a manganese slag-tea oil biochar composite catalyst.
[0036] (4) Degradation of organic matter (ethyl p-hydroxybenzoate): The pH value of organic wastewater was 6.89; the concentration of manganese slag-tea oil biochar composite catalyst added to organic wastewater was 2 g / L; the amount of PMS added was 5 mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20 mg / L; during the degradation reaction, the degradation reaction temperature was 30 °C, the degradation reaction time was 180 min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180 min, the degradation rate of ethyl p-hydroxybenzoate was 77%.
[0037] Example 3
[0038] (1) Pretreatment of manganese slag: first add oxalic acid for 2 h, then add quartz and calcine at 250 °C for 4 h, soak in deionized water for 5 h, and dry at 120 °C for 14 h;
[0039] (2) The tea oil shell was crushed, ground, washed three times with deionized water, dried, loaded into a quartz tube, placed in a high-temperature tube furnace, and heated at a rate of 10 °C / min to 550 °C for 3 h under N2 conditions to obtain raw tea oil shell biochar.
[0040] (3) The manganese slag treated in step (1) and the original tea oil shell biochar obtained in step (2) are used to prepare a composite catalyst: the manganese slag and tea oil shell biochar are combined by a one-pot method and a thermal decomposition process to prepare a manganese slag-tea oil biochar composite catalyst, the same mass of manganese slag and tea oil shell biochar powder are added to 50mL Na2CO3 solution (5g / L) and reacted in an oscillator for 40min, then 1mL HNO3 is added to a beaker, the reaction is continued for 40min, and then dried at 120°C for 10h, and then ground and sieved through a 100-mesh sieve. After grinding, it is loaded into a quartz tube and placed in a high-temperature tube furnace. The temperature is increased at a rate of 10°C / min under the condition of N2 (10mL / min) to 550°C for continuous pyrolysis for 5h to obtain a manganese slag-tea oil biochar composite catalyst.
[0041] (4) Degradation of organic matter (ethyl p-hydroxybenzoate): The pH value of organic wastewater was 6.89; the concentration of manganese slag-tea oil biochar composite catalyst added to organic wastewater was 3 g / L; the amount of PMS added was 10 mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20 mg / L; during the degradation reaction, the degradation reaction temperature was 20°C, the degradation reaction time was 180 min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180 min, the degradation rate of ethyl p-hydroxybenzoate was 100%.
[0042] Comparative Example 1
[0043] In order to demonstrate the degradation effect of manganese slag-tea oil biochar composite catalyst on organic matter under Fenton-like reaction, the catalyst prepared in Example 1 was directly used to adsorb organic matter, the pH value of organic wastewater was 6.89; the catalyst was added to the organic wastewater at a concentration of 2 g / L, and the concentration of ethyl p-hydroxybenzoate in the organic wastewater was 20 mg / L; during the degradation reaction, the degradation reaction temperature was 25°C, the degradation reaction time was 180 min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180 min, the degradation rate of ethyl p-hydroxybenzoate was 5% (such as Figure 1 shown).
[0044] Comparative Example 2
[0045] In order to demonstrate the degradation effect of manganese slag-tea oil biochar composite catalyst on organic matter under Fenton-like reaction, PMS was used to directly oxidize organic matter alone. The pH value of organic wastewater was 6.89; the amount of PMS added was 5mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20mg / L; during the degradation reaction, the temperature of the degradation reaction was 25℃, and the degradation reaction time was 180min. The degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180min, the degradation rate of ethyl p-hydroxybenzoate was 11% (such as Figure 1shown).
[0046] Comparative Example 3
[0047] In order to demonstrate the degradation effect of manganese slag-tea oil biochar composite catalyst on organic matter under Fenton-like reaction, manganese slag was directly used to degrade organic matter in Fenton-like method, the pH value of organic wastewater was 6.89; the addition concentration of manganese slag in organic wastewater was 2g / L, the addition amount of PMS was 5mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20mg / L; during the degradation reaction, the degradation reaction temperature was 25℃, the degradation reaction time was 180min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180min, the degradation rate of ethyl p-hydroxybenzoate was 50% (such as Figure 1 shown).
[0048] Comparative Example 4
[0049] In order to demonstrate the degradation effect of manganese slag-tea oil biochar composite catalyst on organic matter under Fenton-like reaction, biochar was directly used to degrade organic matter in Fenton-like method, the pH value of organic wastewater was 6.89; the concentration of biochar added to organic wastewater was 2g / L, the amount of PMS added was 5mM, and the concentration of ethyl p-hydroxybenzoate in organic wastewater was 20mg / L; during the degradation reaction, the temperature of the degradation reaction was 25℃, the degradation reaction time was 180min, and the degradation effect of ethyl p-hydroxybenzoate was measured by liquid chromatography. At 180min, the degradation rate of ethyl p-hydroxybenzoate was 30% (such as Figure 1 shown).
[0050] From the specific Figure 1 From the comparison results of the degradation of wastewater in Example 1 and Comparative Examples 1-4, it can be seen that manganese slag-tea-oil biochar + PMS: Example 1, manganese slag-tea-oil biochar: Comparative Example 1, PMS: Comparative Example 2, original manganese slag + PMS: Comparative Example 3, biochar + PMS: Comparative Example 4, the degradation effect of organic wastewater can be well achieved by using the manganese slag-tea-oil biochar composite catalyst / PMS heterogeneous Fenton-like system. This is also inseparable from the specific manganese slag-tea-oil biochar composite catalyst adopted by the present invention. Only after it is well compounded with PMS can a good wastewater treatment effect be achieved.
[0051] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.
Claims
1. A method for preparing a manganese slag-biochar composite catalyst, characterized in that: The steps include: Add manganese slag and tea oil shell biochar powder to Na2CO3 solution and react for more than 30 minutes, then add HNO3 and continue to react for more than 30 minutes, then dry at 100-130℃ for more than 8 hours, and continue pyrolysis at 450-550℃ for more than 3 hours.
2. The preparation method according to claim 1, characterized in that: The manganese slag is pretreated by soaking it in deionized water for more than 4 hours and drying it at 100-130° C. for more than 12 hours.
3. The preparation method according to claim 1, characterized in that: During the pyrolysis process, the temperature is raised to a specified pyrolysis temperature at a rate of 10-12°C / min by passing N2.
4. The preparation method according to claim 2, characterized in that: Before the pretreatment, the manganese slag is pre-treated with a treatment agent for more than 1 hour, and then a curing agent is added to the manganese slag for calcination at 200-300° C. for more than 3 hours.
5. The preparation method according to claim 1, characterized in that: The preparation method of the tea oil shell biochar powder comprises: crushing and grinding the tea oil shell, washing it with deionized water for more than three times, drying it, heating it at a rate of 10°C / min under N2 conditions, and continuously pyrolyzing it at 500-600°C for more than 3 hours.
6. The preparation method according to claim 4, characterized in that: The curing agent is any one or more of quartz and starch.
7. The preparation method according to claim 4, characterized in that: The treatment agent is any one of sodium carbonate, quicklime and oxalic acid or a combination of several of them.
8. The composite catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. The composite catalyst prepared by the method for preparing the composite catalyst according to any one of claims 1 to 7 and the use of the composite catalyst according to claim 8, characterized in that: The composite catalyst and PMS are added to the wastewater for degradation, the degradation reaction temperature is 20-30° C., and the degradation reaction time is 150-200 minutes.
10. The use according to claim 9, characterized in that: The added concentration of the composite catalyst is 2 g / L or more; the added amount of PMS is 5 mM / L or more.